2002
DOI: 10.1159/000064578
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Human Protease Inhibitor on Surgical Stress Induced Immunosuppression

Abstract: Background/Aim: Postoperative tissue injury and immunosuppression can occur after major surgery. In this study, we explore the potential benefits of administering a protease inhibitor to treat immunosuppression caused by surgical stress. Methods: Sixteen patients with esophageal cancer were preoperatively allocated at random into two equal groups. A urinary trypsin inhibitor, ulinastatin (UTI), was intravenously administered to the treatment (UTI) group at a dose of 150,000 U every 12 h from the start of surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 17 publications
(15 reference statements)
0
22
0
Order By: Relevance
“…Previous studies demonstrated that T helper cells decreased and T suppressor cells increased significantly as early as 1 day after surgery [22][23][24] . Many subsequent studies also confirmed that surgery for patients with lung cancer [25] , esophageal cancer [26] , gastric cancer [27,28] and colorectal cancer [29,30] induced immediate severe immunosuppression. For cancer patients, an important function adversely affected by this immunosuppression is the anti-tumor response itself.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies demonstrated that T helper cells decreased and T suppressor cells increased significantly as early as 1 day after surgery [22][23][24] . Many subsequent studies also confirmed that surgery for patients with lung cancer [25] , esophageal cancer [26] , gastric cancer [27,28] and colorectal cancer [29,30] induced immediate severe immunosuppression. For cancer patients, an important function adversely affected by this immunosuppression is the anti-tumor response itself.…”
Section: Discussionmentioning
confidence: 85%
“…Conclusions: The deficiencies in proliferation and cytokine release in response to antigen stimulation demon-ity of inflammatory proteases, including trypsin, plasmin, etc., and to limit the enhanced production of inflammatory cytokines [10,11] . Ulinastatin has been reported [12] to significantly reduce the severity of immunosuppression induced by surgical stress. However, so far, there are few studies in which the effects of ulinastatin on the suppressed cellular immunity during severe acute pancreatitis were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and basic research studies have shown the value of UTI. A clinical study by Sato et al (2002) found that UTI has a corrective effect on immune deficiency-caused surgical stress (Sato et al, 2002); UTI can enhance immune function and improve the immune imbalance in sepsis cases through increasing the ratio of inducer T lymphocytes. In 2009, Huang et al (2009) initiated UTI immunotherapy and revealed that UTI therapy can noticeably improve the quality of life of sepsis patients.…”
Section: Discussionmentioning
confidence: 99%
“…The immune indices in patients, including T lymphocyte counts, T lymphocyte function, and cytokine pro-duction, in the perioperative period were recovered to different extents after the application of UTIs. Consequently, it has been suggested that the UTI improves immune function (Sato et al, 2002;Ma et al, 2006).…”
Section: Introductionmentioning
confidence: 99%